(untitled) (Medical Forum Monthly, 2024)
Objective: To determine risk of cesarean section in induced labour. Study Design: Retrospective observational Place and Duration of Study: This study was conducted at the Department of Obstetrics & Gynaecology, Rehman Medical Institute from January 2018 to December 2018. Materials and Methods: A total of 1875 patients were admitted for induction of labour. Data was collected from labour register and patients record file. All patients were induced with Prostin E2. Maximum of 4 doses at interval of 4 hours with exception of patients with PROM, who were induced with 50µg Misoprostol orally as per ward protocol were given. Data collected included parity, gestational age, indication for induction and indication of cesarean section. Results: There were 102 had emergency cesarean section (23.75 of all induced patients) and 327 (76.3%) patients had normal vaginal deliveries. The most common indication for induction was prolong pregnancies [n=147 (34.2%)] followed by PROM [n=71(16.5%], PIH [n=469 (10.7%)], reduced liquor [n=37 (8.6%)], reduced fetal movements (n=33 (7.6%)] and diabetes [n=33(7.6%)]. The most common indication for cesarean section in induced patients was failed induction [n=53 (51.9%)], followed by prolong second stage [n=30(29.4%)]. The average cesarean section rate (elective + emergency) was 40.7%. The rate of emergency c/section in induced patients was 13.55% in comparison to 15.7% in spontaneous labour. Conclusion: Induction of labour for medical reason is not associated with increase in risk of cesarean section.